Welfare Protection of the Homeless and Poor Senior Citizen under the Destitute Persons Act 1977: A Legal Review: (Perlindungan Kebajikan Warga Emas Gelandangan dan Daif Menurut Akta Orang-Orang Papa 1977: Suatu Tinjauan Perundangan) (Kanun: Jurnal Undang-undang Malaysia, 2021)
Malaysia is reported to be an "elderly" country by 2030. Senior citizens are "jewels in experience", wherefore their welfare rights should be protected under the law or by the public in general. Therefore, this paper discusses the rights of senior citizens to be protected by examining the provisions of the Destitute Persons Act 1977. The study was carried out through library research. Apart from analysing the provisions of the Destitute Persons 1977 Act, reported cases of underprivileged and ill senior citizens in Malaysia were also taken into view. In addition, this article also discusses the role of government agencies in helping senior citizens in need of protection and care, in the form of physical or financial assistance. Finally, this article discusses the actions and recommendations of the government which seeks to draw up an Act specifically aimed at protecting senior citizen welfare rights as a whole.Keywords: Senior citizen, homeless, poverty, destitute, Destitute Persons Act 1977